Molecular identification of sugarcane black bug (Cavelarius excavates) from Pakistan using cytochrome C oxidase I (COI) gene as DNA barcode - Hussain, Khadim; Rashid, Kamran; Hafeez, Faisal; Amad, Ikrma; Ashraf, Muhammad (International journal of tropical insect science, 2020)
Sugarcane is one of the major cash crop whose low productivity is due to low nutrients supply and insect pest attacks. The nutrient requirement may be fulfilled by increasing the amount of fertilizer supplements but pest attack is difficult to control through poisonous chemicals due to their harmful effects on plant growth as well as human health. Recently, sugarcane black bug ( Cavelarius excavates ) was reported to attack sugarcane crop in Pakistan which caused plethora of damages to the crop yield. To control the insect pest, first step is to identify the enemy insect precisely. Therefore, a DNA barcode based study was required for the correct identification of bug species. DNA barcoding is one of the most powerful and sophisticated tools for identifying insects where sequence of mitochondrial gene cytochrome C oxidase I (COI) is used as DNA marker. Sugarcane black bug was sampled and its genomic DNA was subject to PCR for amplification of COI gene. Sanger sequencing of targeted gene was done commercially from Macrogen (South Korea). Sequence analysis revealed that our sequence was first DNA barcode sequence of sugarcane black bug ( Cavelarius excavates ) in the databases. This study will help us to open more ways to understand and controlling sugarcane black bug.